The peak performing professor : a practical guide to productivity and happiness - Robison, Susan, 1945- (San Francisco : Jossey-Bass, 2013)
'Grounded in research on neuroscience, faculty development, work productivity, positive psychology, and resilience, this faculty development guide is filled with the techniques and strategies that go beyond a discussion of work-life balance and teaching tips to offer practical tools for managing the life of the professor while maximizing his or her potential. Faculty who complete the book's exercises are able to anchor their work, roles, and use of time in their most deeply held values, to integrate their personal and professional lives into a seamless garment, and to create a legacy of a life well-lived'--
Includes bibliographical references (p. 281-299) and index.
Keywords: College teaching; College teachers